2016
DOI: 10.1093/ejcts/ezv470
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results of mitral valve surgery for degenerative anterior leaflet or bileaflet prolapse: analysis of negative factors for repair, early and late failures, and survival

Abstract: Patients with ALP or BLP can be submitted to surgery with low mortality and great probability of repair in expert hands. Patients should be operated on at an early phase (asymptomatic or mildly symptomatic), because there is a higher probability of repair and greater benefit on long-term survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
27
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 23 publications
5
27
0
3
Order By: Relevance
“…In the EVER-EST II trial, 5-year data reported that patients included in the surgical group which comprised essentially patients with mitral repair, required mitral re-do surgery during the 5 years of follow-up in 9% of cases. This is higher than previously suggested in the observational studies [33][34][35]. Observational studies tend to underestimate outcomes due to lack of follow-up and underreporting.…”
Section: Limitations Of Transcatheter Plasty and The Case Of Transcatmentioning
confidence: 56%
“…In the EVER-EST II trial, 5-year data reported that patients included in the surgical group which comprised essentially patients with mitral repair, required mitral re-do surgery during the 5 years of follow-up in 9% of cases. This is higher than previously suggested in the observational studies [33][34][35]. Observational studies tend to underestimate outcomes due to lack of follow-up and underreporting.…”
Section: Limitations Of Transcatheter Plasty and The Case Of Transcatmentioning
confidence: 56%
“…Interestingly, in the subgroup of patients with AMLP/BLP, the repair rate increased from 94.8% to 98.4% in asymptomatic or mildly symptomatic patients 24. Moreover, these patients had increased late survival in comparison to those with pre-operative NYHA class III/IV symptoms, and similar survival to the age- and sex-matched population (figure 6).…”
Section: Controversies Surrounding Mitral Valve Repairmentioning
confidence: 90%
“…We have found that the need for MVR in AMLP/BLP was influenced not only by anatomical issues but also by patient’s characteristics and by the performing surgeon’s experience (table 3). 24 …”
Section: ‘Repair-all’ Strategy In All Corners Of Mitral Valve Prolapsementioning
confidence: 99%
“…It is superior to replacement and interventional techniques and has the potential to restore normal life expectancy. 1,2 However, repair techniques may be complex and often dependent on an artistic ability of the operating surgeon. 3,4 This art is important because the impact on survival and symptoms is related to repair success and durability.…”
Section: Torsten Doenst MD Phdmentioning
confidence: 99%